AUTOMATION OF INNOVATIVE DEVELOPMENT MANAGEMENT OF THE RUSSIAN ARCTIC ZONE - O. Klementeva; S. Chernogorskiy; K. Shvetsov (Модернизация, инновация, развитие)
In the industrially developed countries about 80–95% of the GDP increase is provided by new knowledge represented by new technologies and machinery. This transition to the new innovative development became possible with the creation of new technological patterns for organization of R&D, industrial and innovative activities. Despite of the fact that the structures of national and regional innovative systems of diff erent countries have much in common which concerns the components, the functional classifi cation and the interaction procedures, the question of theoretical structural description of the regional innovative system seems to be of importance. The object of research is the interaction between the entities of the Russian Arctic innovative system from the viewpoint of the complex information inputs. The subject of research is the model-algorithmic support of the automated system providing for innovative activities within the Russian Arctic zone.The article is aimed to work out the theoretical and practical methods for automation of the regional innovative system management with application of modern information technologies. In order to achieve the specifi ed goal, the following tasks are solved in the article: determining of the modern methods and approaches of organization and management of the information flows within the contemporary business communities; the analysis and structural description of the regional innovative system; working out of the concept for the complex automated information system supporting the innovative activity. The research methods. For solving of the stated tasks some methods and approaches for creating of the social networks, methods of organization of the information fl ows based on the Web 2.0 technology and some expert methods of innovation were used. Finally, the following results were obtained: the structural description of the regional innovative system has been worked out. The main elements and relations were determined; the concept of creation of the complex automated information system supporting the innovative activity with implementation of Web 2.0 technology has been worked out; the organizational and technological aspects of the appropriate structure and the list of the needed information services for the participants of the innovative activity has been worked out.The practical value of the obtained results is that the main principles for creation of the complex automated information system supporting the innovative activity with implementation of Web 2.0 technology has been worked out and substantiated.The proposed system could be used in the sphere of public administration and coordination of communication and information support of the participants of the innovative activity in the Russian Arctic zone.